Doping polyvinyl alcohol can improve the injectability of biological ceramics in 3D printing and influence the adhesion of cells to the scaffolds after sintering. Issue 18 (15th September 2021) - Lin, ZhiDong; Hu, XuLin; Zhong, LiLun; Peng, DeQiang; Lu, JunLin; He, Jian; Shen, Xiaofei; Xiong, ChengDong; Xu, Tao; Niu, Wei
Abstract: β tricalcium phosphate (β-TCP) is a common biological ceramic in bone tissue engineering due to its excellent biocompatibility and biodegradability. However, owing to its inherent properties of poor injectability and forming ability, the application of TCP in extrusion 3D printing is quite limited. To solve this problem, we innovatively printed gelatin and PVA (Polyvinyl alcohol) binary systems by taking advantage of the ability of gelatin to solidify rapidly at low temperatures and the ability of PVA to effectively improve phase separation during extrusion. Here, we fabricated a series of novel Gel-PVA-TCP scaffolds by incorporating different concentrations of PVA (5%, 10%, 15%) through 3D printing. Collectively, the addition of PVA made differences in three ways. First, compared to the PVA-free system, the novel printing system significantly improved the printability of TCP paste. The printing temperature was decreased to 35–45 °C by doping different concentrations of PVA. Next, the novel printing system maintained the excellent forming ability and printing precision of the scaffolds. Compared to the macropores of scaffolds without doping PVA (456.1 ± 11.2 μm), the macropores of Gel-PVA-TCP were 486.1 ± 26.5, 446.1 ± 15.2, and 443.7 ± 26.3 μm. Last, after sintering, the scaffolds with different concentrations of PVA exhibited similar compressive strength (3.82 ± 0.22, 3.34 ± 0.23, 3.74 ± 0.38, 3.47 ± 0.48 Mpa) and distinct micropores (4.44 ± 0.7, 1.54 ± 0.3, 2.59 ± 0.6, 3.59 ± 1.0 μm) on the surfaces of the scaffolds. Moreover, it was found that differences in the microstructure significantly facilitate the adhesion of bone marrow mesenchymal stem cells to scaffolds. Hence, the methods we provided hold a great promise for application in 3D printing techniques. Graphical abstract: Image 1